Therapeutic Approaches to Dysthymia (Global Journal of Medical Research, 2022)
dysthymia is a psychic disorder defined by chronic lowering of mood with a minimum duration of two years in which fluctuating moments of the emotional state oc- cur Unlike the clinical picture of major depressions dysthymia has milder manifestati- ons which occur in a non-episodic manner Even with milder symptoms dysthymia ends up having a significant impact on patients lives since in the vast majority of cases the diagnosis is made too late It is a disease that affects 3 to 6 of the world population mainly individuals in early adulthood being twice as common in women than in men The prognosis of this psychic disorder is associated with the chronicity of the disease and the possible co-morbidities resulting from the depressive condition Objective the objective of this work is to analyze the literature collected about dysthymia and the possible thera- peutic approaches for the pathology